2015
DOI: 10.3389/fnagi.2015.00076
|View full text |Cite
|
Sign up to set email alerts
|

Learning of bimanual motor sequences in normal aging

Abstract: While it is well accepted that motor performance declines with age, the ability to learn simple procedural motor tasks appears to remain intact to some extent in normal aging. Here we examined the impact of aging on the acquisition of a simple sequence of bimanual actions. We further asked whether such learning results from an overall decrease in response time or is also associated with improved coordination between the hands. Healthy young and old individuals performed a bimanual version of the classic serial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 70 publications
(88 reference statements)
7
20
3
Order By: Relevance
“…These results corroborate prior unilateral evidence that implicit learning is preserved with aging while explicit learning declines [78]. Switch cost times (change in response time when the sequence was switched between hands) were also examined [76], [77]. Older adults demonstrated greater switch cost times at baseline, which were thought to be reflective of reduced IHI or less asymmetric cortical activation for motor planning and execution.…”
Section: Motor Learning Implications For Rehabilitationsupporting
confidence: 80%
See 1 more Smart Citation
“…These results corroborate prior unilateral evidence that implicit learning is preserved with aging while explicit learning declines [78]. Switch cost times (change in response time when the sequence was switched between hands) were also examined [76], [77]. Older adults demonstrated greater switch cost times at baseline, which were thought to be reflective of reduced IHI or less asymmetric cortical activation for motor planning and execution.…”
Section: Motor Learning Implications For Rehabilitationsupporting
confidence: 80%
“…Two investigations used a bimanual sequence learning task to assess motor learning differences between young and older adults [76], [77]. One used an implicit learning approach and illustrated no learning deficit in the older group [76], while the other used an explicit learning approach and found that older adults demonstrated reduced motor learning [77].…”
Section: Motor Learning Implications For Rehabilitationmentioning
confidence: 99%
“…The remaining 12 studies support the model of age invariance with findings of relatively spared procedural learning in ageing. In line with the baseline speed problem evident in the studies with children, one study has found that initial greater learning-related gains in raw RTs in older adults disappeared after normalizing the RT data (i.e., Bhakuni & Mutha, 2015). Two studies have reported that although learning is evident later in the task, older adults need more practice to show sequence-specific learning in RT measures compared to young adults (Daselaar, Rombouts, Veltman, Raaijmakers, & Jonker, 2003;Fraser, Li, & Penhune, 2009).…”
Section: Typical Developmentmentioning
confidence: 80%
“…Importantly, this was true despite higher baseline RTs in the older adults in both studies, which makes correcting for baseline speed arguable. The findings regarding accuracy are mixed, with one study reporting no age differences (Bhakuni & Mutha, ), four studies reporting higher accuracies for younger adults (i.e., Daselaar et al ., ; Foster & Giovanello, ; Fraser et al ., ; Verneau, van der Kamp, Savelsbergh, & de Looze, ), and three studies reporting higher accuracies for older adults (i.e., Bo, Jennett, & Seidler, ; Howard & Howard, , ).…”
Section: Typical Developmentmentioning
confidence: 99%
“…How can age-related differences in these lower level (perceptual-motor) processes affect task-general and task-specific learning? It has been suggested that slower responses generally provide 'more room to improve' during practice (e.g., Bhakuni & Mutha, 2015;Jiang, Capistrano, Esler, & Swallow, 2013). According to this argument, participants with initially slower response times should exhibit a greater speed-up (i.e., task-general learning) during practice compared to others with initially faster response times.…”
Section: Introductionmentioning
confidence: 99%